2007
DOI: 10.1007/s00109-006-0137-2
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential and mechanism of kinetin as a treatment for the human splicing disease familial dysautonomia

Abstract: Mutations that affect the splicing of pre-mRNA are a major cause of human disease. Familial dysautonomia (FD) is a recessive neurodegenerative disease caused by a T to C transition at base pair 6 of IKBKAP intron 20. This mutation results in variable tissue-specific skipping of exon 20. Previously, we reported that the plant cytokinin kinetin dramatically increases exon 20 inclusion in RNA isolated from cultured FD cells. The goal of the current study was to investigate the nature of the FD splicing defect and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 50 publications
4
76
0
1
Order By: Relevance
“…[3][4][5][6][7][8] This modification has mainly been shown in splicing mutations giving a percentage of wildtype transcripts from the mutated allele, which is also described as having a 'leaky' effect. In a previous collaborative study in which kinetin corrected aberrant splicing for the most common splicing mutation in familial dysautonomia (FD), we also demonstrated that kinetin was able to restore normal splicing for one NF1 mutation (c.6724C4T, exon 36) in a minigene splicing model, 9 which encouraged us to extend our research to other mutations. In this study, we evaluated the effect of kinetin and of four other drugs (valproic acid (VPA), sodium butyrate (SB), (À)-epigallocatechin gallate (EGCG) and aclarubicin), which were previously found to modify splicing in other genetic disorders, in cell lines derived from patients harboring 19 different NF1 splicing mutations to evaluate their putative use as therapeutic agents for NF1.…”
Section: Introductionmentioning
confidence: 54%
See 3 more Smart Citations
“…[3][4][5][6][7][8] This modification has mainly been shown in splicing mutations giving a percentage of wildtype transcripts from the mutated allele, which is also described as having a 'leaky' effect. In a previous collaborative study in which kinetin corrected aberrant splicing for the most common splicing mutation in familial dysautonomia (FD), we also demonstrated that kinetin was able to restore normal splicing for one NF1 mutation (c.6724C4T, exon 36) in a minigene splicing model, 9 which encouraged us to extend our research to other mutations. In this study, we evaluated the effect of kinetin and of four other drugs (valproic acid (VPA), sodium butyrate (SB), (À)-epigallocatechin gallate (EGCG) and aclarubicin), which were previously found to modify splicing in other genetic disorders, in cell lines derived from patients harboring 19 different NF1 splicing mutations to evaluate their putative use as therapeutic agents for NF1.…”
Section: Introductionmentioning
confidence: 54%
“…Interestingly, cell lines from the patient with mutation c.6724C4T showed less evident exon 36 inclusion that the minigene model from our previous study. 9 Differences in the splicing behavior of minigenes and primary cell lines have been reported in literature, which highlights the importance of the surrounding genomic region in determining the splicing. 10,11 Moreover, the heterozygosity of cell lines derived from patients vs homozygosity in constructions should be taken into account when comparing data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is evidence that the clinical severity of these disorders is influenced by splicing efficiency. Therapeutic strategies that target the correction of splicing defects are under development for spinal muscular atrophy, familial dysautonomia, and cystic fibrosis (Nissim-Rafinia et al 2004;Hims et al 2007;Hua et al 2008). The molecular basis for individual variation in splicing efficiency is largely unknown, but identification of the responsible factors could facilitate the development of therapies.…”
Section: R187xmentioning
confidence: 99%